Research on Orthogonal Direction Algorithm Using Direction Error - Jun-fang Guo; Yong-feng Zhi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
For the orthogonal direction algorithm, the iteration direction is the direction vector, and the iteration error of the adaptive filter is caused by the input vector. These two directions are not the same one, which leads to more deviation for the iteration error. In this paper, an orthogonal direction algorithm using direction error is presented to settle this problem, which the iteration error is caused by the iteration direction. By setting the weight error to be zero in the direction vector, the optimal step-size is obtained, which improves the adaptive filtering convergence rate. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4216